Extending the MODPATH Algorithm to Rectangular Unstructured Grids. Issue 1 (5th March 2015) - Pollock, David W.
Abstract: The recent release of MODFLOW‐USG, which allows model grids to have irregular, unstructured connections, requires a modification of the particle‐tracking algorithm used by MODPATH. This paper describes a modification of the semi‐analytical particle‐tracking algorithm used by MODPATH that allows it to be extended to rectangular‐based unstructured grids by dividing grid cells with multi‐cell face connections into sub‐cells. The new method will be incorporated in the next version of MODPATH which is currently under development.